Methods of Sociological Research - McNeil, Lori (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Course Objective: To provide an introduction to basic sociological methods including exposure to the most common qualitative and quantitative methodological designs. Through lectures, exams, in-class exercises, experiments and activities, class discussions, the construction of a research proposal and report and the texts, students will be encouraged to develop and test social research questions and hypothesis. This will be a hands-on course in which students will design, conduct and analyze their own research project.